Aksi Kamisan Sebagai Representasi Civil Society dan Respon Pemerintah Era Susilo Bambang Yudhoyono Menyikapi Kasus Pelanggaran Hak Asasi Manusia (HAM) Masa Lampau - Rendy Adiwilaga (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2018)
This research is motivated by the phenomenon of routine peaceful actions every Thursday in front of the state palace, which is commonly called the kamisan action. Kamisan itself was motivated by the attitude of the government which kept quietly addressing and following up on violations of Human Rights (HAM) in the archipelago. In this study, the author uses the theory of social action proposed by Kotler 5C, namely Cause, Change Agency, Target Change, Channel, and Change Strategy. The research method used in writing this study is a descriptive research method with a qualitative approach. The results of the study showed that the Victim Solidarity Network for Justice (JSKK) was dominated by victims of justice. Then the target, the first is, so that the president will form a presidential decree related to resolving cases of human rights violations in Indonesia that have not been resolved, and take the initiative to re-run the adhoc court to try suspects who are now free without trial. Then the attorney general is expected to be able to objectively decide the cases of human rights violations that have occurred and have not been resolved as gross human rights violations, and the last is for the DPR to take the initiative to recommend the presidential decree to the president. Finally, the next target is that the community "reminds" the government in resolving cases of human rights violations in Indonesia. Unfortunately, this kamisan action is still weak in terms of quality and quantity, considering that the coordination between the members of the Kamisan action itself is still weak, supported by the government who is a suspect of impunity, which in the end produces movement goals that are difficult to achieve.